A Roadmap to Advance Marine and Coastal Monitoring, Biodiversity Assessment, and International Reporting: A Developing Nation Perspective - Smit, Kaylee P; Van Niekerk, Lara; Harris, Linda R.; McQuatters-Gollop, Abigail; Shannon, Lynne J.; Sink, Kerry J. (Frontiers in Marine Science, 2022)
Despite the increasing number of tools and indicators to measure biodiversity status and trends, many developing countries struggle to initiate and advance coastal and marine assessments needed to monitor and track national and international progress in biodiversity targets. We identified five key challenges that hinder progress in this context, based on a national marine assessment workshop held in South Africa, and developed recommendations and tangible actions to address these challenges drawing from multiple national assessments, regional initiatives, and global collaborations over the last 15 years. Challenges include a poor understanding of methods, limited capacity and funding for assessments, a lack of systematic approaches to biodiversity assessment and indicator development, and scattered efforts that often fail to link science to policy. Key actions could enable the development of a coordinated framework to feed into policy and decision-making at multiple scales. We provide South African examples to highlight a developing country’s progress toward marine biodiversity assessment and provide a roadmap to integrated monitoring, assessment, and reporting based on positive outcomes. Recommendations to address challenges include building collective understanding of assessment tools and methods, prioritizing pressures urgently needing mitigation measures, using relevant indicators to support reporting at multiple scales, applying coordinated approaches to identify gaps and opportunities, codeveloping coordinated approaches with direct policy links, and leveraging resources and technical capacity for iterative improvement. This roadmap can guide developing and developed countries and support global best practices to collaboratively advance marine and coastal ecosystem monitoring and assessment at multiple scales for meeting many objectives.